SOSIALISASI MANFAAT DAN PEMBUATAN NATTO DAN SOY YOGURT MELALUI KEGIATAN WEBINAR DAN PRAKTEK - Sumarsih, Sri; Baktir, Afaf (Jurnal ABDI: Media Pengabdian Kepada Masyarakat, 2021)
Natto and Soy Yogurt are fermented food products that are very beneficial for improving health. This community service activity aims to socialize the benefits and make them known to the wider community. However, community service activities during the Covid-19 pandemic cannot be carried out face-to-face and have activities with the community in large numbers. Therefore, this community service activity was carried out through webinar and practical activities. Online seminars was chosen so that the coverage was wider and more people could participate in the pandemic. Face-to-face and community activities are carried out with a limited number of participants, according to health protocols. The level of success, benefit and acceptance of the community from this community service activity is known from the responses of the participants during the activities. Based on the results of the assessment/ response of participants who were present virtually and those present at the location, In general it can be concluded that the PKM activity entitled "socializing the benefits and making natto and soy yogurt through webinars and practices" is going well, but better preparation is still needed.The material presented by the resource person is suitable for the current pandemic conditions, easy to understand, easy to practice and can be developed for home businesses. The Zoom Meeting application can be used as a medium for community service activities in pandemic conditions even though it still cannot reach the wider community. Â Keywords: Socialization, natto, soy yogurt, webinar, practical